On the stability of a climate model for an Earth-like planet with land-ocean coverage. (29th June 2018) - Alberti, T; Lepreti, F; Vecchio, A; Carbone, V
Abstract: The discovery of potentially habitable Earth-like exoplanets orbiting around hosting stars increased the interest in investigating their climate systems. In this perspective, we study the stability properties of a simple energy balance climate-vegetation model. It describes the interaction between the planetary surface, that can be partially covered by vegetation, a large ocean and a land surface. The model allows to investigate changes in response to variations in the hosting star's irradiance (e.g. due to mutual distance variations). The stability properties of the system change according to variations of the control parameters, as for example the effective growth rate of vegetation γ and the stellar distance a . In particular, the model presents both stable and unstable fixed points, which can exhibit several kinds of stability properties depending on the distance of the planet from the hosting star.